A View from Two Benches : Bob Thomas in Football and the Law - Feldmann, Doug, 1970- (Book collections on Project MUSE., 2020)
"The story of Bob Thomas, a man who reached the very top of two separate and distinct professions, Chicago Bears' football and the law, while guided along the way by an underpinning of faith"--